ChemInform Abstract: Application of the Lithiation—Borylation Reaction to the Rapid and Enantioselective Synthesis of the Bisabolane Family of Sesquiterpenes. Issue 2 (9th January 2013) - Aggarwal, Varinder K.; Ball, Liam T.; Carobene, Simon; Connelly, Rickki L.; Hesse, Matthew J.; Partridge, Benjamin M.; Roth, Philippe; Thomas, Stephen P.; Webster, Matthew P.
Abstract Starting materials (I) and (V) are prepared from the corresponding ketones by means of Noyori′s transfer‐hydrogenation procedure.